Crystal and magnetic structure and cation distribution of Mn2-xV1+xO4 spinels (x = 0, 1/3 and 1) - Pannunzio Miner, Elisa Victoria (2009)
We synthesized the spinel-type compounds belonging to the Mn2-xV1+xO4 series with x = 0, 1/3 and 1 as polycrystalline powders. Crystal and magnetic structures were refined using synchrotron X-ray and neutron powder diffraction. At 300 K all members crystallize in the cubic system, space group F d over(3, ̄) m, and show a structural transition at low temperature, changing to a tetragonal symmetry (space group I41/amd). Cations distributions between octahedral and tetrahedral sites were refined from neutrons diffraction (ND) data and explained based on crystal field stabilization energies (CFSE) and ionic radii. The magnetic unit cell is the same as the crystallographic one, having identical symmetry relations. The magnetic structure was refined as an arrangement of collinear spins, antiferromagnetically ordered, parallel to the c-axis of the unit cell. The refined site magnetic moments are smaller than those obtained from hysteresis cycles of the M vs. H measurements, indicating that some non-collinear disordered component coexists with the ordered component along the c-axis.